Association of genetic polymorphisms in the C19orf66 gene and biochemical indices of HBV infected individuals in Yunnan - Liu, Ni; Liu, Min; Yang, Jun; Dong, Shuwei; Yue, Ming; Huang, Peng; Xia, Xueshan; Zhang, A-Mei (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction Hepatitis B virus (HBV) infection causes serious liver diseases and is a healthy problem worldwide. Although vaccines are administered to infants after birth, there is no effective medicine for HBV infection. The interferon-stimulated genes (ISGs) are important factors in the host that can aid in restraining the virus, and the C19orf66 gene has a wide-antiviral spectrum. Methods In this study, three SNPs in the C19orf66 gene were sequenced and genotyped, and their potential function were predicted and further verified by dual-luciferase reporter assay. Results Although no significant difference of genotype and allele frequency was observed between HBV patients and the controls, the genotype and allele frequency showed significant difference between HBV patients with HBsAg-positive and HBV patients with HBsAg-negative or controls. Genotype AA (P= 0.009) and AT (P= 0.019) of rs77076061 showed higher and lower frequency in HBV patients with HBsAg-positive than in patients with HBsAg-negative, respectively. Genotype AG of rs1979262 played a risk role in HBV patients with HBsAg-positive (13.22%) than in patients with HBsAg-negative (7.53%, P= 0.036) or controls (8.48%, P= 0.033). The frequency of allele A of rs1979262 was higher in patients with HBsAg-positive (6.61%) than in patients with HBsAg-negative (3.77%, P= 0.042), while it was the opposite for the allele G. Moreover, the associations between genotypes of SNPs in the C19orf66 gene and the ALT, AST, and DBIL level were also identified. The functional assay suggested that the SNPs might influence the C19orf66 expression by changing the connection of transcriptional factors. Conclusion In summary, the association between genetic polymorphisms in the C19orf66 gene and HBV infection/biochemical indices of patients was firstly identified in Yunnan Province.